Simulator Sick but Still Immersed: A Comparison of Head-Object Collision Handling and Their Impact on Fun, Immersion, and Simulator Sickness - Ziegler, Peter; Roth, Daniel; Knots, Andreas; Kreuzer, Michael; Von Mammen, Sebastian (25th IEEE Conference on Virtual Reality and 3D User Interfaces, VR 2018 - Proceedings, 2018)
We compared three techniques for handling head-object collisions in room-scale virtual reality (VR). We developed a game whose mechanics induce such collisions which we either addressed (1) not at all, (2) by fading the screen information to black, or (3) by restricting translation, i.e. correcting the virtual offset in such a way that no penetration occurred. We measured these conditions' impact on simulator sickness, fun, and immersion perception. We found that the translation-restricted method yielded the greatest immersion value but also contributed the most to simulator sickness.
CRIS-Team Scopus Importer:2021-03-29
Keywords: Human-centered computing-Empirical studies in visualization; Human-centered computing-Virtual Reality